Odpowiedzi

2010-03-14T17:26:24+01:00
3a+4=a-1+a+7
3a-a-a = -1+7-4
a = 2

10-2b+6-b=10-b+4-b
-2b-b+b+b = 10+7-10-6
-b = 1 / : (-1)
b = -1
1 1 1
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-03-14T17:27:23+01:00
3a+4=a-1+a+7
3a-a-a=-1+7-4
a=6-4
a = 2

10-2b+6-b=10-b+4-b
-2b-b+b+b=10+4-10-6
-b=-2
b=2



pamiętaj, że przenosząć liczę na drugą strone równania/nierówności zmienia się znak na przeciwny ! ;)
1 1 1
2010-03-14T17:29:21+01:00
3a+4=a-1+a+7
3a-a-a=-4-1+7
a=4

10-2b+6-b=10-b+4-b
-2b-b+b+b=-10-6+10+4
2b=18/2
b=9
1 1 1